Evolved galaxies at z > 1.5 from the Gemini Deep Deep survey: The formation epoch of massive stellar systems - McCarthy, P; Le Borgne, D; Crampton, D; Chen, H; Abraham, R; Glazebrook, K; Savaglio, S; Carlberg, R; Marzke, R; Roth, K; Jorgensen, I; Hook, I; et al. (Institute of Physics Publishing, 2004)
We present spectroscopic evidence from the Gemini Deep Deep Survey for a significant population of color-selected red galaxies at 1.3 < z, < 2.2 whose integrated light is dominated by evolved stars. Unlike radio-selected objects, the z > 1.5 old galaxies have a sky density greater than 0.1 arcmin-2. Conservative age estimates for 20 galaxies with z > 1.3. 〈z〉 = 1.49, give a median age of 1.2 Gyr and 〈z f〉 = 2.4. One-quarter of the galaxies have inferred z f > 4. Models restricted to [Fe/H[ ≤ 0 give median ages and zf of 2.3 Gyr and 3.3, respectively. These galaxies are among the most massive and contribute ∼50% of the stellar mass density at 1 < z < 2. The derived ages and most probable star formation histories suggest a high star formation rate (∼300-500 M⊙, yr-1) phase in the progenitor population. We argue that most of the red galaxies are not descendants of the typical z ∼ 3 Lyman break galaxies. Galaxies associated with luminous submillimeter sources have the requisite star formation rates to be the progenitor population. Our results point toward early and rapid formation for a significant fraction of present-day massive galaxies.